The Supervision of Legality by the Finnish Parliamentary Ombudsman during the COVID-19 Pandemic - Farzamfar Mehrnoosh; Salminen Janne (Nordiska administrativa förbundet (NAF), 2022)
This article studies the supervisory role of the Finnish Parliamentary Ombudsman during the COVID-19 pandemic in 2020. A major legal problem during emergencies is that respect for the rule of law tends to get lost in the midst of rapid decision-making procedures. Therefore, in addition to the parliamentary control and the judicial review of courts, the Ombudsman finds a complementary position in supervising the legality of public actions during emergencies. The annual report of the Finnish Parliamentary Ombudsman shows that 931 complaints arrived this Office in 2020, concerning issues on the COVID-19 pandemic. These cases have tested public actions against the Finnish Constitution and other laws during the pandemic. To analyse the legal supervisory role of the Ombudsman during this period, we have selected three themes including restrictions on the freedom of movement, imposing visit bans on care centres, and limiting business activities. This analysis exposes the nature of the COVID-19 pandemic as a societal syndemic, meaning that although the health-related aspect of this crisis prevailed initially, the use of public power may not only endanger the principle of legality, but also cause societal, economic, and political changes, which may last for years after the crisis.